The Contribution of Self Efficacy to Entrepreneurial Interest through Motivation As An Intervening Variable - Hendrayanti, Silvia; Fauziyanti, Wachidah (Universitas Negeri Semarang, 2021)
The unemployment rate specifically those who graduated from universities is still increasing and is high. Since university graduates must have adequate abilities and expertise, they should be able to get jobs or to create their jobs. Based on an observation conducted in several universities in Semarang, the percentage of students in universities who are interested in entrepreneurship is quite high. However, several factors hinder their desire to be entrepreneurs. Hence, it requires more in-depth research. This study aims to examine the contribution of self-efficacy towards the students’ entrepreneurship interest through motivation as an intervening variable. The population of this study was the students of the economics faculty of universities in Semarang who had taken entrepreneurship courses while the sample was 97 students. The analysis tool used was Structure Equation Models with Partial Least Square approach. The results showed that Self-efficacy had a positive and significant effect on students’ motivation with a t-value of 28,573>1.96 and motivation also has a positive and insignificant effect on entrepreneurial interest with a t-value of 0.502<1.96. Furthermore, Self-efficacy also has a positive and significant effect on entrepreneurial interest with a t-value of 4.528>1.96 and it strongly affects entrepreneurship interest through Motivation as an Intervening variable.